(untitled) (GYMNASIUM, 2008)
Rugby football, often just "rugby", may refer to a number of sports descended from a common form of football developed at Rugby School in England, United Kingdom. Rugby league, rugby union, American football and Canadian football are modern sports that originated from rugby football. Rugby league and rugby union are the only two sports referred to as "rugby" today.